Socialism a very short introduction - Newman, Michael 1946- (Oxford Oxford University Press, 2005)
"Michael Newman examines and explains the successes and failures of modern socialism by taking an international perspective - ranging from communism in Cuba to social democracy in Sweden." "Discussing its evolution from the industrial towns of the 19th century to its response to the feminist, Green, and anti-capitalist movements today; Newman concludes that, with its values of equality, solidarity, and cooperation, socialism remains as relevant as ever but that it needs to learn lessons from the past."--Book Jacket.
Socialist traditions -- Cuban communism and Swedish social democracy -- New lefts-enrichment and fragmentation -- Socialism today and tomorrow.
Includes bibliographical references (pages 155-162) and index.
Keywords: Socialism